STEM challenge: two years of community-engaged engineering. Issue 1 (25th April 2020) - Hite, Rebecca; Spott, Jessica; Johnson, Levi; Sobehrad, Lane
Abstract : Purpose: Community-engaged partnerships have the ability to combine expertise and resources to enhance the local STEM learning ecosystem, by engaging the actors in communities that can enhance students' experiences in science, technology, engineering and mathematics (STEM) education. Texas Tech University (TTU) and Lubbock Independent School District (LISD) have partnered to coordinate an annual STEM Challenge to encourage STEM learning and interest among local middle grade students. Each summer, teams of (three to four) students from ten LISD middle schools participate in a week-long engineering design challenge, facilitated by TTU undergraduate mentors and their teachers, structured by the Engineering Design Process (EDP). Design/methodology/approach: Quantitative (survey) and qualitative (open-ended responses) data from two years of student glider and hovercraft projects offer insight into how 66 students developed STEM knowledge and leveraged 21 st -century skills to accomplish a shared aim (design challenge). Findings: Findings suggest growth in students' 21 st -century skills, most among underrepresented (racial, ethnic and gender minority) groups. Data from year one (2018) informed year two (2019) in both programming and the research, including enhanced training for mentors and a deeper exploration of students' experiences during each stage of the EDP during the STEM challenge. Originality/value: Significant and salient findings are discussed along with recommendations for both programmatic and methodological improvements for year three (2020). This study provides insight into how to structure similar community-engaged partnerships in enhancing the community STEM ecosystem through collaborative STEM experiences for diverse, younger learners.